Non-reciprocal photonics based on time modulation - Sounas, Dimitrios L.; Alù, Andrea (Nature photonics, 2017)
Reciprocity is a fundamental principle in optics, requiring that the response of a transmission channel is symmetric when source and observation points are interchanged. It is of major significance because it poses fundamental constraints on the way we process optical signals. Non-reciprocal devices, which break this symmetry, have become fundamental in photonic systems. Today they require magnetic materials that are bulky, costly and cannot be integrated. This is in stark contrast with most photonic devices, including sources, modulators, switches, waveguides, interconnects and antennas, which may be realized at the nanoscale. Here, we review recent progress and opportunities offered by temporal modulation to break reciprocity, revealing its potential for compact, low-energy, integrated non-reciprocal devices, and discuss the future of this exciting research field. The progress on non-reciprocal photonic devices enabled by temporal modulation is reviewed.